Meta-Analisis Pengaruh Model Example Non Example dalam Pembelajaran IPA di Sekolah Dasar - LUIS KOMALA; LALU HAMDIAN AFFANDI; BAIQ NISWATUL KHAIR (GANEC SWARA, 2021)
The purpose of this study was to analyze the effectivenees of the effect od the example non example model on science learning. The research method used is a meta-analysis of previous studies that apply the example non example learning model in science learning. The research begins with formulating a research problem, tracing the relevant research results for analysisi. Data is collected by browsing electronic journals via google scholar. Form the search, it was obtained 8 scientific articles that have been published, the instrument was in the form of coding based on predetermined criteria. Data were analyzed using the effect size. The research findings reveal that overall the studies conductes are effective and effective on science learning in elementary scools with an effect size of 1,323132 or in the high efficiency category. The example non example model also has an effect and is effective at the grade level, namely in grade 4,5 and 6 and the application of learnin to improve learning outcomes, critical thinking skills, and the ability to explain.  The conclusion of this study is that the example non example model is more effective in science learning compared to other learning models from this study.